Effects of Different Lipase Inactivation Treatments on Physicochemical Properties of Naked Oat Globulins. Issue 3 (17th November 2015) - Gao, Yichao; Wang, Lili; Qiu, Ju; Bai, Guangling; Li, Zaigui
Abstract : Lipase inactivation is an essential treatment for oat processing, because of the negative effects of lipase on nutrient preservation and storage extension. The effects of different lipase inactivation treatments including hot air roasting, infrared roasting, normal‐pressure steaming, and high‐pressure steaming on the physicochemical properties of oat globulins were investigated. Results showed that normal‐pressure steaming had little effect on solubility of oat globulins; hot air roasting increased foaming capacity of oat globulins but did not change their foaming stability; and all the inactivation treatments increased the surface hydrophobicity and content of total sulfhydryls of oat globulin but decreased exposed sulfhydryl groups. In addition, oat globulin granules from the hot air roasting treatment were distributed more evenly in oat globulin powder compared with the control group. All treatments except normal‐pressure steaming changed the molecular weight of oat globulin subunits, which made the bands of 66, 000 and 45, 000 disappear from SDS‐PAGE. These results indicated that normal‐pressure steaming was ideal to maintain good solubility of oat globulins, and hot air roasting was ideal to maintain relatively good foaming properties. The treatments changed physicochemical properties of oat globulins by influencing protein aggregation and subunit composition that resulted in different content of sulfhydryl groups and surface hydrophobicity.